Energy cost of running in well-trained athletes: toward slope-dependent factors - Lemire, M.; Remetter, R.; Hureau, T. J.; Geny, B.; Lonsdorfer, E.; Favret, F.; Dufour, S. P. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This study aimed to determine the contribution of metabolic, cardiopulmonary, neuromuscular, and biomechanical factors to the energy cost (ECR) of graded running in well-trained runners.